Gambaran tingkat pengetahuan mahasiswa tentang pencegahan penularan covid-19 - Marliyana, Marliyana; Pangesti, Dimas Ning; Septiana, Ria (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2024)
Background: The prevalence of COVID-19 in Indonesia is 488,000 cases. Students' knowledge about preventing COVID-19 transmission contributes to breaking the chain of transmission. Purpose: To determine the characteristics of students' knowledge levels about preventing COVID-19 transmission at the Baitul Hikmah Nursing Academy in Bandar Lampung in 2021. Method: This descriptive study used a non-random sampling technique with 30 students as respondents. Data were collected using a questionnaire completed via Google Forms, consisting of 30 items, and analyzed using a frequency distribution formula. Results: 19 (63%) students' knowledge level regarding COVID-19 transmission prevention at the Baitul Hikmah Nursing Academy met the following criteria: good (19%), adequate (9) (30%), and inadequate (2) (7%). Conclusion: The level of student knowledge regarding COVID-19 transmission prevention at the Baitul Hikmah Nursing Academy in Bandar Lampung in 2021 was categorized as good. Recommendation: Further in-depth research should be conducted to examine student attitudes and behaviors regarding COVID-19 transmission prevention. Keywords: COVID-19; Transmission Prevention; Student Knowledge. Pendahuluan: Prevalensi Covid-19 di Indonesia 488.000 kasus, Pengetahuan mahasiswa tentang pencegahan penularan Covid-19 berkontribusi untuk memutus mata rantai Covid-19. Tujuan: Untuk mengetahui karakteristik tingkat pengetahuan mahasiswa tentang pencegahan penularan covid-19 di akademi keperawatan baitul hikmah bandar lampung tahun 2021. Metode: Penelitian bersifat deskriptif menggunakan teknik non random sampling dengan jumlah responden 30 mahasiswa. Data dikumpulkan menggunakan kuesioner yang diisi melalui google form yang terdiri dari 30 item pernyataan dengan data dianalisis menggunakan rumus distribusi frekuensi. Hasil: Terdapat kriteria tingkat pengetahuan mahasiswa tentang pencegahan penularan Covid-19 di akademi keperawatan baitul hikmah, baik 19 (63%), cukup 9 (30%), kurang 2 (7%) . Simpulan: Gambaran tingkat pengetahuan mahasiswa tentang pencegahan penularan Covid-19 di akademi keperawatan baitul hikmah bandar lampung tahun 2021 dalam kategorik baik. Saran: Dapat melakukan penelitian lebih dalam lagi dengan tema melihat sikap atau prilaku mahasiswa tentang pencegahan penularan Covid-19. Kata Kunci: Covid-19; Pencegahan Penulara; Pengetahuan Mahasiswa.